SOME ISSUES OF THE LEGISLATIVE PRACTICE OF APPLYING THE STATE BUILDING CODE (SBC) B.2.2-12: 2019 «PLANNING AND DEVELOPMENT OF TERRITORIES» - Kiuntsli Р.; Stepaniuk А.; Besaha І. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
The issues of planning and development of territories in the context of public administration is the subject of research in thed various fields of scientific knowledge. However, special investigations into the law use and law enforcement of the SBC, which establish technical requirements for the planning and development of territories, are almost absent. The present article is devoted to highlighting the key nuances of legal practice for law enforcement and compliance with the requirements of the SBC in the field of planning and development of territories, their validity over time and importance as a normative source. It is established that the main problems of using SBC in the field of planning and development of territories are related to: 1) lack of understanding of the principles of regulations in time; 2) differences in the semantic load of the general and special permitting principle of legal regulation; 3) disregard for the blanket nature of the rules governing legal liability in the field of construction. According to the results of the study, it is concluded that non-governmental entities can use SBC in their own activities, which have expired, as a source of additional information (by analogy with scientific or educational materials). The conditions of such application are: 1) there is no current normative act (in particular, SBC), which regulates the relevant relations – sets requirements for the object of regulation; or 2) in the case of a valid normative document, it does not regulate public relations in the part in which the repealed SBC applies. In the exercise of their powers, law enforcers can use only the legal act that is in force at the time of the emergence and existence of certain legal relations. The repealed act will not be applicable. This mechanism of legal acts effect follows from the constant change of social relations, their conditionality by economic, social, political, etc. factors. Accordingly, the legislator's approach to regulating such relations is changing: some acts, due to the loss of their social danger, cease to be punished, others, on the contrary, are recognized as more dangerous and responsibility for them increases.